Omental Nodular Deposits of Recurrent Chromophobe Renal Cell Carcinoma Seen on FDG-PET/CT - Win,Aung Zaw; Aparici,Carina Mari
We present the case of a 69-year-old male with chromophobe renal cell carcinoma (RCC). Chromophobe RCC accounts for only 4% of renal cancers and it is the least aggressive type. Omental nodular deposits due to RCC metastasis are very rare and it is reported only in more aggressive forms of RCC. This is the first report that shows FluoroDeoxyGlucose – Positron Emission Tomography/Computed Tomgraphy (FDG-PET/CT) images of omental nodular deposits from chromophobe RCC. FDG-PET/CT is becoming very useful in restaging RCC with distant metastases.